Model altruism in improving organizational performance in social welfare institutions ministry of social affairs of the republic of Indonesia - Fatchur Rohman; Noermijati Noermijati; Mochamad Soelton; Mugiono Mugiono (Cogent Business & Management, 2022)
This paper aims to evaluate the impact and analyze the effect of transformational Leadership on organizational performance mediated by organizational Commitment, Transformational Leadership, and organizational Commitment moderated by Altruism. This research was conducted using a descriptive method at the A-certified Child Welfare Institution (LKSA) in Indonesia with a sample of 185 respondents. The approach used in this research is Structural Equation Model (SEM) with Partial Least Square (PLS) 3.0 analysis tool. This finding shows that altruism towards organizational Commitment is not able to improve organizational performance even though altruism has been included as a counterweight, meaning that it increases the welfare of others without realizing it for one's benefit. It should be expected that the altruistic individual cares and wants to help even when no benefits are offered or there is no hope of getting them back. Other findings suggest that the benefits are more than just altruistic when transformational Leadership exhibits high levels of altruism. Altruistic behavior is judged relative to the norm and has the potential for much better organizational performance.
Keywords: 650; altruism; organizational Commitment; organizational performance; transformational leadership